(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Background : TB is a major public health problem. Though Investigation and chemotherapy is free of cost we are still facing poor compliance and severe degree of disease among the poorly treated ones. We have tried to explore into reasons behind it. Methodology : It was a retrospective cross- sectional study done at Biratnagar Sub-metro Politian City. Result : People accept DOTS. They visit as early as they are referred but are diagnosed lately. They have multiple reasons to quit the treatment before completion. Conclusion : We found that early diagnosis and proper counselling about the need of prolonged regime of treatment and its side effects are important factors in preventing transmission and poor compliance. Keywords: TB; DOTS; HIV; BPKIHS; cases; defaulters DOI: 10.3126/saarctb.v7i1.3957 SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(1) 13-18